Integrasi Aspek Spiritualitas dalam Pembinaan Karakter SDM: Suatu Telaah Literatur - Indah Siti Nurhalizah; Zainal Berlian; Baharudin (STKIP Subang, 2026)
This study aims to analyze the integration of spirituality in character development of Human Resources (HR) through a Systematic Literature Review (SLR) approach. The study examines peer-reviewed articles published, retrieved from reputable academic databases. The selection process follows the PRISMA 2020 guidelines to ensure methodological transparency and rigor. The findings indicate that spirituality functions as a source of meaningful work, moral reinforcement, and intrinsic motivation that contribute to individual character formation. The concepts of workplace spirituality and spiritual leadership show positive relationships with work engagement, organizational commitment, psychological well-being, and HR performance. The integration of spiritual values into HR management policies and practices fosters an organizational culture grounded in integrity, responsibility, and sustainability. This study concludes that spirituality-based character development represents a holistic approach relevant to addressing contemporary organizational challenges. Further empirical research is recommended to examine contextual models of spirituality integration in HR development.